In silico analysis and transcript levels of non-specific lipid transfer proteins (SiLTPI.5 and SiLTPII.1) under abiotic stresses in sesame (Sesamum indicum) - Baiya, Supaporn; Kitjaruwankul, Sunan; Juntaropakorn, Methee; Promkatkaew, Malinee (Agriculture and Natural Resources, 2023)
Importance of the work: Non-specific lipid transfer proteins are found in all land plants; however, there have been no published articles on computational analysis or gene expression under different abiotic stresses of sesame (Sesamum indicum). Objectives: To demonstrate the ligand-binding interaction of lipid molecules with the proteins of SiLTPI.5 and SiLTPII.1 and to examine the transcript levels of these corresponding genes in response to salt, chilling, heating, salicylic acid and abscisic acid. Materials & Methods: The spatial structures of SiLTPI.5 and SiLTPII.1 were simulated using the SWISS-MODEL server. Then, molecular docking of these modeled structures with 22 ligands was executed and molecular dynamics (MD) simulations of the docked protein-ligand complex (SiLTPs-[ergo]sterol) were completed. Quantitative real-time polymerase chain reaction of SiLTPs under abiotic stress was carried out using gene-specific primers. Results: The overall structure of SiLTPI.5 consisted of four helices, four loops and a long C-terminal with a 310-helix. SiLTPII.1 consisted of five helices, an N-terminal 310-helix and a C-terminal with a short polyproline type II. SiLTPI.5 and SiLTPII.1 with ΔG values of -6.92 kcal/mol and -6.87 kcal/mol, respectively, could likely bind with (ergo)sterol rather than other lipid molecules. The MD simulations confirmed that the SiLTPs-ligand complexes were maintained and stabilized via hydrophobic force and hydrogen bonding. Finally, the SiLTPI.5 and SiLTPII.1 genes were significantly regulated after abiotic treatments. Main finding: The SiLTP-lipids interactions were stabilized via conserved amino acid with hydrophobic side chains around the binding region, together with some hydrogen bonds between the protein and ligand. The SiLTPI.5 and SiLTPII.1 genes play a crucial role in stress responses.